Therapeutic inhibition of RBM20 improves diastolic function in a murine heart failure model and human engineered heart tissue - Radke, Michael; Badillo-Lisakowski, Victor; Britto-Borges, Thiago; Kubli, Dieter A.; Jüttner, René; Parakkat, Pragati; Carballo, Jacobo Lopez; Hüttemeister, Judith; Liss, Martin; Hansen, Arne; Dieterich, Christoph; Mullick, Adam E.; et al. (Science translational medicine, 2021)
Heart failure with preserved ejection fraction (HFpEF) is prevalent and deadly, but so far, there is no targeted therapy. A main contributor to the disease is impaired ventricular filling, which we improved with antisense oligonucleotides (ASOs) targeting the cardiac splice factor RBM20. In adult mice with increased wall stiffness, weekly application of ASOs over 2 months increased expression of compliant titin isoforms and improved cardiac function as determined by echocardiography and conductance catheter. RNA sequencing confirmed RBM20-dependent isoform changes and served as a sensitive indicator of potential side effects, largely limited to genes related to the immune response. We validated our approach in human engineered heart tissue, showing down-regulation of RBM20 to less than 50% within 3 weeks of treatment with ASOs, resulting in adapted relaxation kinetics in the absence of cardiac pathology. Our data suggest anti-RBM20 ASOs as powerful cardiac splicing regulators for the causal treatment of human HFpEF.
Gesehen am 19.01.2022